Telecommunications cables design, manufacture, and installation - Hughes, Harold (John Wiley & Sons, 1997)
Drawing from a wealth of first-hand experience of cable design, construction and emplacement, the author provides a working assessment of the development and performance characteristics of optical fibres, and metal or alloy cables.